M1 Concordance to asthma medications in patients receiving long-term Omalizumab treatment. (14th November 2013) - Elsherbiny, MS; Mitchell, V; Mansur, AH; Afridi, L; Ahitan, B
Abstract : Introduction: It is estimated that 5% of adult asthma patients have uncontrolled asthma despite high dose corticosteroid therapy. Omalizumab is a monoclonal anti-IgE antibody that has been shown to improve asthma control. 1 As asthma control improves, concordance to other prescribed asthma medication may decline which may undermine omalizumab effectiveness. The extent of such non-concordance is explored in this study. Methods: The records of40 patients receiving long-term omalizumab treatment have been reviewed for concordance. Medication history was retrieved for all patients, which included all prescriptions issued by their General Practitioner over most recent twelve months, detailing the doses and the number of tablets and/or inhalers patients received. Patients were classified as non-concordant if their medication history showed less than 75% adherence. Concordant and non-concordant groups were compared in relation to asthma control questionnaire (ACQ), Fractional exhaled nitric oxide (FeNO), forced expiratory volume in one second (FEV1), and number of asthma related admissions and frequency of severe steroid requiring asthma exacerbations at baseline line of omalizumab treatment. Results: Sufficient information was only available for 25 patients (20 female) receiving long-term omalizumab treatment with a mean age of 44 years (range 19 to 68 years) and mean weight of 78kg (SD = 20.78). The prevalence of non-concordance was 64% (n = 16). All non-concordant patients had 50% or less prescription filling history. Overall non-concordant patients had a higher FEV1 before starting omalizumab treatment (mean FEV1 = 1.865, 95% predicted) compared to concordant patients (mean FEV1 = 1.401, 95% predicted), better ACQ scores (mean = 2.26), less number of patients on oral steroids (56.25% n = 9) compared to (66.7% n = 6). Conclusion: The prevalence of non-concordance in patients receiving long-term omalizumab treatment is high and may undermine treatment effectiveness. The non-concordant patients had overall less severe asthma than concordant patients. Further research is needed to determine the effect of such non-concordance on the effectiveness of omalizumab in the long term. Reference: Efficacy and safety of a recombinant anti-immunoglobulin E antibody (omalizumab) in severe allergic asthma. Holgate ST, Omalizumab 011 International Study Group.